Avaliação da influência de revestimento em compósito cimentício dúctil e sustentável no reforço de alvenaria estrutural - Veronese, Renato Baiochi Alves (Universidade Federal de São Carlos, 2021)
This work aims to evaluate the use of a reinforcement system to strengthen structural masonry panels under vertical and lateral load. The reinforcement system is the Eco-friendly Ductile Cementitious Composite (EDCC). This is a ductile material used for repair and reinforcement of structural masonry walls. The first part of methodology consists in analyzing the structural behavior of masonry reinforced with EDCC, based on experimental test results performed by the research group. The study assessed the influence of the EDCC on masonry compression, flexure, and shear strength. The second part of the methodology consists of finite element modelling of the experimental tests, to calibrate valid models for the correct simulation of the tests. It was possible to determine accurate models simulating the behavior of masonry coated with EDCC submitted to compression, flexure, and shear loads. A formulation to predict the coated masonry compression load capacity is derivate from the models results. The models and the experimental tests returned positive values in relation to the use of EDCC with reinforcement material, showing that there is an increase in strength and ductility of the walls with the increase of the EDCC layer.
Evaluation of the influence of ductile and sustainable cement composite coating on structural masonry reinforcement
Keywords: Modelagem em elementos finitos; Alvenaria estrutural; Reforço; EDCC; Finite element modelling; Structural masonry; Reinforcement; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL